2017
DOI: 10.1007/s40520-017-0747-2
|View full text |Cite
|
Sign up to set email alerts
|

The 13-year observation of hip fracture in Poland—worrying trend and prognosis for the future

Abstract: IntroductionHip fractures are often considered to be one of the most common osteoporotic fractures. In our previous study, we noted the increasing trend in the total number of hip fractures as well as crude and standardized rates, for both women and men. This observation enabled us to delve deeper into the study of osteoporotic fractures.MethodsHospital records between 1.01.2002 and 31.12.2014 with ICD-10 codes S72.0. S72.1 and S72.2 (femoral neck. intertrochanteric, subtrochanteric, and inter and subtrochante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
3
12
0
3
Order By: Relevance
“…In France, decreasing trends were found both in crude incidence rates and especially age- standardized rates despite the increased global number of HF throughout a 12-year period (11). Recent data from Poland showed an increasing trend in the total number of HF and incidence rates, in both women and men (12,13). In general, incidence rates decreased in the last 2 decades after a period of significant increase in many Western European countries and Northern America, albeit at different times, whereas rates are still increasing in other parts of the world (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…In France, decreasing trends were found both in crude incidence rates and especially age- standardized rates despite the increased global number of HF throughout a 12-year period (11). Recent data from Poland showed an increasing trend in the total number of HF and incidence rates, in both women and men (12,13). In general, incidence rates decreased in the last 2 decades after a period of significant increase in many Western European countries and Northern America, albeit at different times, whereas rates are still increasing in other parts of the world (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 97%
“…No published national data span more than a year in Poland [5]. Most reports come from a minority of hospitals or regional data extrapolated nationally [4,13]. Czerwinski et al [5] published data for 2005 based on discharge codes reported to the NHF with an estimated annual number of HFs of 17,199.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent work published by Wilk et al [4] covers 13-year data from a single region in Southern Poland. Their observations for 2014 estimated the crude incidence rate to be 216.2 (men, 140.9; women, 276.5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations